Efeito do tipo de éter amina na hidrofobicidade do quartzo no processo de flotação catiônica reversa de minério de ferro - Pierre Azevedo Fernandes (2017)
The cationic reverse flotation route is one of the main processes to remove quartz from iron ore. The ether amines are the most common surfactant used to modify quartzs surface hydrophobicity from hydrophilic to hydrophobic. Beyond the traditional differentiation between ether monoamines and ether diamines, these reagents may have other differences as raw materials source, carbon chain length and type and neutralization degree. The definition of the best ether amine for a given iron ore is commonly performed through empirical testwork only. The target of this work is to contribute for a better scientific understanding about the ether amine type effect on quartz hydrophobicity in iron ore cationic reverse flotation process. The pKa value (pH where collectors molecular and ionic species have equal concentration) for different ether amine types where determined and quartz floatability was investigated at different pH conditions, different collector concentration and type, in the presence and absence of an iron minerals depressant. The effect of carbon chain length and differences between ether monoamines and ether diamines for quartz floatability were clarified for distinct flotation conditions. In the absence of depressant, the maximum quartz floatability was achieved at pH corresponding to the collectors pKa. In these conditions, the ether diamines provide higher quartz hydrophobicity than the ether monoamine. With depressant, the maximum quartz floatability was achieved at pH values higher than the collectors pKa. In these conditions, the ether monoamine provides higher quartz hydrophobicity than the ether diamines and the collector with longer carbon chain length was stronger than the one with shorter carbon chain length